2019
DOI: 10.1021/jacs.9b02505
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, X-ray Crystallography and Antiviral Activity of Allosteric Inhibitors of Flavivirus NS2B-NS3 Protease

Abstract: Flaviviruses, including dengue, West Nile and recently emerged Zika virus, are important human pathogens, but there are no drugs to prevent or treat these viral infections. The highly conserved Flavivirus NS2B-NS3 protease is essential for viral replication and therefore a drug target. Compound screening followed by medicinal chemistry yielded a series of drug-like, broadly active inhibitors of Flavivirus proteases with IC 50 as low as 120 nM. The inhibitor exhibited significant antiviral activities in cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
142
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(143 citation statements)
references
References 35 publications
0
142
0
1
Order By: Relevance
“…The docking results of the four protein targets ( Figure 4 ) showed that the two potent compounds, dibromopinocembrin ( TH011 ) and dibromopinostrobin ( TH002 ), preferentially interacted at the SAM-binding site of NS5 MTase, in which their binding energy of −9.0 kcal/mol slightly exceeded that of sinefungin that is commonly used to inhibit the DNA MTases. Although the pinostrobin and one of pinocembrin analogs were previously reported to be active against NS2B-3 pro and NS5 pol, respectively [ 21 , 24 ], none of the halogenated analogs in this study could bind to these targets stronger than their parent compounds TH022 and TH019 , as well as the compound 9 [ 25 ] and NITD-107 [ 26 ], which were protease and NS5 Pol inhibitors, respectively. Besides, the binding affinity of TH011 and TH002 at both kl loop and Y site of the DENV E protein were relatively lower than that of the potent flavanone FN5Y [ 11 ] in consistent with no fusion inhibition observed ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The docking results of the four protein targets ( Figure 4 ) showed that the two potent compounds, dibromopinocembrin ( TH011 ) and dibromopinostrobin ( TH002 ), preferentially interacted at the SAM-binding site of NS5 MTase, in which their binding energy of −9.0 kcal/mol slightly exceeded that of sinefungin that is commonly used to inhibit the DNA MTases. Although the pinostrobin and one of pinocembrin analogs were previously reported to be active against NS2B-3 pro and NS5 pol, respectively [ 21 , 24 ], none of the halogenated analogs in this study could bind to these targets stronger than their parent compounds TH022 and TH019 , as well as the compound 9 [ 25 ] and NITD-107 [ 26 ], which were protease and NS5 Pol inhibitors, respectively. Besides, the binding affinity of TH011 and TH002 at both kl loop and Y site of the DENV E protein were relatively lower than that of the potent flavanone FN5Y [ 11 ] in consistent with no fusion inhibition observed ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 74%
“… Binding affinity (kcal/mol) for the studied pinocembrins ( TH022 and TH011 ) and pinostrobins ( TH019, TH002, TH012, and TH018 ) in comparison with the known inhibitors of DENV protein targets: E protein at kl loop and Y site (FN5Y [ 11 ]), NS2B-3 pro at allosteric site (compound 9 [ 25 ]), NS5 MTase at SAM binding site (Sinefungin [ 27 ]), and NS5 Pol at the active site (NITD-107 [ 26 ]), predicted by molecular docking method using AutoDock VinaXB. …”
Section: Figurementioning
confidence: 99%
“…Hence, to overcome such situation presently, available more resources, much faster, and advance scientific techniques need to be adopted and explored. Earlier, a number of studies have proposed various traditional and specific methods for the identification of different chemical entities and demonstrated their selective inhibition mechanism and inhibitory efficacy against NS3‐NS2B protease complex at different levels …”
Section: Introductionmentioning
confidence: 99%
“…Unlike those inhibitors targeting the protease active site, allosteric inhibitors were developed by stabilizing the inactive conformation of the protease [133]. With a screening of a library containing compounds targeting lysine specific demethylase 1, an allosteric inhibitor with a IC 50 of 120 nM was developed ( Figure 7) [134]. The inhibitor binding site was confirmed by solving its co-crystal structures.…”
Section: Allosteric Protease Inhibitorsmentioning
confidence: 99%